Providing digital human resource management model - Seyed Reza Akramian; amin nikpour; Hamid Reza Mollaei; Mohammad Jalal Kamali; Hojjat Talebi (مدیریت و چشم انداز آموزش)
Abstract The purpose of this research is to provide a model of digital human resources management with a data-based approach. The current research is applicable-developmental in terms of purpose, descriptive in terms of information gathering, and qualitative in terms of the nature of the data. The statistical population of the research includes specialists and experts familiar with digital human resource management topics. Sampling in this research was snowball type. Based on the subject of the desired data; through preliminary studies, semi-structured interviews, collection, and sampling continued until reaching theoretical saturation. The obtained information was analyzed with MAXQDA2020 software. The results showed that the digital human resources management model with the data-based approach includes causal factors (technological, environmental, human, and organizational), background factors (digital platform, management platform, and individual platform), intervening factors (cultural factors and creation of platforms new), strategies (organizational and managerial), and consequences (individual, cultural, and organizational), which is necessary, according to the mentioned model, while paying attention to the multiplicity, to provide the ground for the implementation of the desired situation. Extended abstract Introduction Globalization and the rapid growth of information and communication technology have faced a fundamental change in the process of human resources management; and the role and function of human resources has been marginalized with the colorful presence of information and communication technology, and it is even feared that one day human resource management will be without role-playing. Man should be realized in all fields and organizational dimensions. Planning, organizing, directing and controlling intelligent and digitized human capital and virtual space accelerates and facilitates its processes (Momeni Mehmoui, 2024). The process of digital transformation is one of the new tricks in the field of human resources management, which has recently gained double importance with the spread of the corona virus in our country and among some government organizations and businesses in the field of digital and technology. Due to the fact that the corona situation has brought an unprecedented crisis to the world undergoing digital transformation, millions of people have started to work remotely to prevent the spread of the disease and maintain the continuity of business, and the development of virtual human resources and alternative work strategies helped organizations to adapt to the current challenges and to prepare for future disruptions. Therefore, one should seek to analyze the role of human resources development in the crisis and transition to a new period, so that in case of disruption and change, one can always help one's organizations not only to survive this crisis, but also in a new period of work transformed by technology, progress, and increase their performance (Bennett et al, 2021). Despite the fact that the importance of digital human resources in advancing the goals of the organization has been established, very few studies have been done in this field so far, which indicates the existence of a theoretical and research gap in this subject area. Therefore, it is expected that by presenting a comprehensive model, this research can pave the way for a smooth path during the successful entry and movement of the banking sector and other organizations towards digital transformations. According to what has been said, the gig economy has imposed new requirements in all fields, especially human resource management, on the government sector, among which digitalization can be pointed to, which deserves to be given a suitable transformative response. Therefore, the digital management of human resources can be considered as a requirement for the government sector for a major transformation in the gig economy (Vrontis et al, 2021). For this purpose, this research tries to provide a digital model of human resources management in the banking network of Iran in line with this necessity and specify what features this model should have and how it should be designed and implemented (Malekzadeh & Sadeghi, 2016). In order to achieve this purpose, in the research process using the qualitative method and also having the opinions of experts, an attempt is made to answer the question: how the model of digital human resources management is with the data-based approach and how reliable it is? Theoretical literature Concepts such as "digitalization", "digital transformation" or "digital disruption" are currently discussed among the most prominent researches. In general, such concepts indicate the increasing use of technology and related fundamental changes in many areas of business and society, which is also true (Martins, 2022). Digital human resources management is a way of thinking that continuously provides digital technologies for more productivity of employees and building a better work experience for them (Ghader & Shami Zanjani, 2019). Research background Hosseinpour & HamzeNouripour (2023) in a research titled human resource management without humans, functions of digital transformation, challenges and solutions (a transformational approach to human resource management in the age of information and communication technology), have shown that although modern tools such as analysis big data will overshadow the way human resources are managed, it will not replace the insight of managers. Technology can help fill the gaps in the field of using human resources properly as a competitive advantage in business. Rastgar et al, (2022) in a research with the aim of intelligent human resources management: explaining the requirements and technology-oriented platforms in knowledge-based companies reported that intelligent strategic management has the highest degree of centrality among the variables and after that intelligent leadership has the highest centrality, and regarding the highest degree of output as the most influential variable on the modeling done, we can point to the intelligent strategic management. Research methodology The current research method is data-based analysis. The statistical population of the research includes specialists and experts familiar with digital human resource management topics. The researcher first examined the research topic qualitatively with limited participants and then, based on the qualitative findings, he proceeded to build the desired tool. The technique used in sampling in this research was snowball type. Based on the topic of data and information through preliminary studies, the semi-structured interviews were collected, and sampling continued until reaching the theoretical saturation and sufficiency, and after conducting 15 interviews, the data analysis indicated that no new data was added to the previous data, because high percentage of the data extracted from the last interviews were repetitive; therefore, after conducting 15 interviews and reaching theoretical saturation, the interviews were ended. According to the data-based strategy, a list of concepts and categories was collected and a model related to the topic was compiled in three open, central and selective coding techniques. The full text of the interviews was conducted with MAXQDA software and three experts outside the research were consulted to ensure the transferability of the research findings. Research findings The results showed that the digital human resources management model with the data-based approach includes causal factors (technological, environmental, human and organizational), background factors (digital platform, management platform, and individual platform), intervening factors (cultural factors and creation of platforms new), strategies (organizational and managerial), and consequences (individual, cultural and organizational). Discussion and conclusion The purpose of this research was to present a model of digital human resources management with the data-based approach. The findings of the research showed that the human resource management model includes causal factors (technological, environmental, human and organizational), background factors (digital platform, management platform, individual platform), intervening factors (cultural factors and creation of new platforms), strategies (organizational and management), and consequences (individual, cultural and organizational). These findings are in line with the results of Tijan et al, (2021), (Vallicelli et al, (2018), Vrontis et al, (2021), and Malekzadeh & Sadeghi (2016). Based on the model obtained from the digital human resources management with the data-based approach and its dimensions, the implementation of the digital human resources management depends on the correct understanding of the causal conditions. In the explanation of these results, it can be said that if the causal conditions are not properly identified in an organization and are not paid attention to, all the strategies presented are prescriptive and lose their ability and efficiency over time. In the presented model of the current research; among the causal factors, organizational (clarity of the information structure in the organization) and human (human factors) components have been given more attention in this section. Based on the presented model, background conditions have also been observed along with the causal factors in digital human resources management with the effective data-based approach. Among these factors, components such as the material and spiritual support of the government, the suitability of the society's culture with the individual's culture, and the degree of integration of digital human resources stakeholders have received the attention of the interviewees. In explaining these results, we can mention the impact of the context and environment in which an organization plays a role, which is more important in relation to private sectors. Another dimension in this model is the dimension of consequences based on the opinion of the interviewees in the management of digital human resources with the data-based approach; based on which, cultural consequences (proper training of human resources employees) and organizational consequences (human resources department, in creating and maintaining a positive image of digital systems) has received more attention. In terms of the strategic dimension, the interviewees paid the most attention to organizational strategy (strategic system of communication with clients and individual perspective of human resources management) in digital human resources management with a data-based approach. In this model, this category is of the type of action and solution and does not have the aspect of a process, and from this point of view, paying attention to these factors in the strategy of digital human resources management can be helpful. In terms of the intervening conditions, the interviewees were more focused on creating new (digital) platforms (independence of managers and having new ideas), which can play an effective role in providing a successful model in terms of digital human resources management with the data-based approach. In terms of the central phenomenon, the interviewees focused on the category of digital learning and paid less attention to other assumed components, which are among the factors that should be considered in order not to create a disturbance in the selection of effective solutions for digital human resource management with the data-based approach.